Evaluation of the Effect of Soil Fertility Management Scenarios on the Amount of Available Nitrogen, Phosphorus, and Potassium in Soil in Six Consecutive Cultivations - S.A. Ghaffari Nejad; F. Moshiri; S.M. Mousavi (علوم آب و خاک, 2025)
This study was conducted to evaluate soil fertility management scenarios including separate use of chemical and organic fertilizers (animal manure and municipal waste compost) and their integrated application on changes in the amount of available nitrogen, phosphorus, and potassium in the soil from November 2017 for four years in six consecutive crops at the Agricultural Research Station of the Soil and Water Research Institute. The results showed a depletion of 14 and 44% of soil available nitrogen and phosphorus, and no depletion of available potassium in the treatment without fertilizer in six consecutive cultivations. Annual consumption of 20 t ha-1 of municipal waste compost and 75% of the recommended nitrogen showed the highest amount of soil-available nitrogen. Unlike phosphorus, the amount of soil available nitrogen in municipal waste compost treatments was significantly higher than in cattle manure. The highest available soil phosphorus was in the treatment with 10 t ha-1 of cattle manure before each crop, and the average available phosphorus in six consecutive cultivations was significantly higher than in the other treatments. The use of 10 t ha-1 of cattle manure and municipal waste compost before each crop resulted in the highest accumulation of potassium in the soil, respectively. The available soil potassium in cattle manure treatments was significantly higher than in municipal waste compost. The results of this experiment indicated the importance of using fertilizers containing nitrogen, phosphorus, and potassium in maintaining soil fertility stability in the long term.